UJI KERAPATAN TANAM DAN DOSIS POLARIS DENGAN SISTEM TOT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L) - Triyono, Kharis - (Joglo)
ABSTRACT The research is intended to know the effect of plant density and Polaris herbicide dosage applied in no tillage system on the growth and the yield of corn (Zea mays L). The highest weight of grains per plot (3153,54 g) per plot is achieved by the combination of plant density of 75 x 20 cm and Polaris dosage of 4 l/ha, and the lowest (1844,16 g) per plot is obstained by the combination of plant density of 75 x 30 cm and Polaris dosage of 2 l/ha Key word : plant density, Polaris herbicide, no tillage, corn